A trial Of Immunisation Against Cutaneous Leishmaniasis - Mohammed A. Kadir; Hussein S.A. Al-Obaidi; Ghanim A. Al-hula; Abdul-Ghani M. AI-Samarai (مجلة كلية الطب, 2006)
Background: Cutaneous leishmaniasis is an endemic protozoal disease in Iraq. Recovery from the disease confers a solid and permanent immunity. Vaccination with a living inoculum of promastigotes isolated from culture reduce the incidence of disease. Objective: To show the efficacy of different types of antigens for protection of Balb/c mice against cutaneous leishmaniasis. Methods: Thirty Balb Ic mice were divided in to six groups, groups 1-4 were immunized with different types of antigens (heat killed, freezing-thawing, formalin fixed and ultrasonicated). Received June 2005 Group 5 was treated with freshly harvested viable promastigotes from liquid medium as positive Accepted Nov. 2005 control and group 6 was kept as negative control. Leishmanin test was used for estimation of hypersensitivity of skin. Results: Immunization with antigens preparation revealed that, the immunized mice became resistant to infection. Conclusion: Immunization of mice against cutaneous leishmaniasis is possible by using different types of antigens. Key words: Immunisation, cutaneous leishmaniasis, mice.